2004
DOI: 10.1128/iai.72.4.2434-2437.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protein Serine/Threonine Kinase StkP Positively Controls Virulence and Competence in Streptococcus pneumoniae

Abstract: In the Streptococcus pneumoniae genome, stkP, encoding a membrane-associated serine/threonine kinase, is not redundant (L. Novakova, S. Romao, J. Echenique, P. Branny, and M.-C. Trombe, unpublished results). The data presented here demonstrate that StkP belongs to the signaling network involved in competence triggering in vitro and lung infection and bloodstream invasion in vivo. In competence, functional StkP is required for activation of comCDE upstream of the autoregulated ring orchestrated by the competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
167
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(176 citation statements)
references
References 22 publications
(33 reference statements)
8
167
1
Order By: Relevance
“…Homologs of PrkC in some pathogenic streptococci are required for full virulence in animal models of infection (21,23), suggesting that the streptococcal PrkC homologs regulate the expression or activity of virulence factors in their respective hosts. These streptococcal PrkC homologs each exhibit a PrkClike bipartite domain architecture including PASTA domains, suggesting that, like E. faecalis PrkC, they detect perturbations of the cell envelope as sensory input.…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of PrkC in some pathogenic streptococci are required for full virulence in animal models of infection (21,23), suggesting that the streptococcal PrkC homologs regulate the expression or activity of virulence factors in their respective hosts. These streptococcal PrkC homologs each exhibit a PrkClike bipartite domain architecture including PASTA domains, suggesting that, like E. faecalis PrkC, they detect perturbations of the cell envelope as sensory input.…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of PrkC have also been implicated in S. pyogenes adherence and invasion and in E. faecalis persistence (72,82). The involvement of eSTKs in virulence has also been reported for several other pathogens, such as Streptococcus pneumoniae, E. faecalis, Pseudomonas aeruginosa, and Salmonella enterica serovar Typhi (33,43,46,(144)(145)(146)191).…”
Section: Estks In Bacteriamentioning
confidence: 99%
“…A strain in which stkP is deleted is still viable in vitro but grows more slowly, is less competent for genetic transformation, and is more susceptible to several environmental stresses (29)(30)(31)(32). StkP also plays an essential role for in vivo survival, because stkP mutants were strongly attenuated in virulence in mouse models (29,30). Phenotypic analysis, through both transmission electron microscopy and differential interference contrast microscopy, showed that stkP mutants often are elongated, suggesting a defect in cell division (30,33).…”
mentioning
confidence: 99%
“…PASTA domains of StkP were shown to bind synthetic and native PG subunits and β-lactam antibiotics (28). A strain in which stkP is deleted is still viable in vitro but grows more slowly, is less competent for genetic transformation, and is more susceptible to several environmental stresses (29)(30)(31)(32). StkP also plays an essential role for in vivo survival, because stkP mutants were strongly attenuated in virulence in mouse models (29,30).…”
mentioning
confidence: 99%